Light rare earth sulfide modified cuprous sulfide thermoelectric material, preparation method and application thereof, and hot pressing sintering mold

The preparation method of cuprous sulfide thermoelectric material modified by light rare earth sulfide solves the problems of copper ion segregation and insufficient thermal stability of cuprous sulfide thermoelectric material, improves its thermoelectric conversion performance, and makes it suitable for medium and high temperature temperature difference conversion environment.

CN120622926APending Publication Date: 2025-09-12NANYANG NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510656158.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-21
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

In practical applications, cuprous sulfide thermoelectric materials have problems of copper ion segregation and insufficient thermal stability, which affect their thermoelectric conversion performance.

Method used

Light rare earth sulfide and cuprous sulfide powders are mixed and cold pressed and hot pressed to prepare light rare earth sulfide modified cuprous sulfide thermoelectric material. The localized characteristics of the 4f electron layer and the high melting point of light rare earth sulfide are utilized to form a heterojunction interface, thereby improving the thermal stability and thermoelectric transport performance of the material.

Benefits of technology

The thermal stability and thermoelectric conversion performance of cuprous sulfide thermoelectric materials are improved, making them suitable for medium and high temperature temperature difference conversion environments, reducing thermal conductivity and enhancing carrier transfer efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120622926A_ABST
    Figure CN120622926A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of thermoelectric materials, and particularly relates to a light rare earth sulfide modified cuprous sulfide thermoelectric material, a preparation method and application thereof and a hot pressing sintering mold. The preparation method of the light rare earth sulfide modified cuprous sulfide thermoelectric material comprises the following steps: (1) crushing light rare earth sulfide, then adding cuprous sulfide powder, mixing and crushing, and sieving to obtain a solid mixture; (2) carrying out cold press molding treatment on the solid mixture to obtain a molded material block; (3) the formed material block is placed in a hot pressing sintering mold, pre-pressure is applied to the formed material block, and an assembled mold material block is obtained; and (4) placing the assembled mold material block in a quartz tube of a tubular furnace, carrying out hot pressing sintering treatment in an inert atmosphere, and cooling to obtain the light rare earth sulfide modified cuprous sulfide thermoelectric material. The light rare earth sulfide modified cuprous sulfide thermoelectric material disclosed by the invention has both thermal stability and thermoelectric transport characteristics, and is good in comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of thermoelectric materials, and in particular relates to a light rare earth sulfide modified cuprous sulfide thermoelectric material, a preparation method and application thereof, and a hot pressing sintering mold. Background Art

[0002] Cuprous sulfide (Cu2S) has attracted widespread attention as a low-cost, environmentally friendly thermoelectric material due to its high electrical conductivity and low thermal conductivity. However, in practical applications, Cu2S suffers from problems such as copper ion segregation and insufficient thermal stability, which limits further improvement of its performance.

[0003] During the service of the cuprous sulfide thermoelectric device, due to the thermal stress driven by the temperature gradient and the electric field, the copper ions (Cu + ) exhibits liquid-like migration characteristics, leading to dynamic structural instability and thermal fatigue accumulation within the material. This significantly impacts the electronic transport properties of copper ions, making it difficult to maintain these properties under temperature gradients. Consequently, directional diffusion occurs in the thermo-electric coupling field, forming localized copper-rich regions and vacancy defects. Therefore, the thermoelectric conversion performance of pure cuprous sulfide is still insufficient to meet the requirements of many applications. To compensate for the thermal stability shortcomings of cuprous sulfide, the addition of reinforcing phases is often used to improve its thermal stability and thermoelectric conversion performance.

[0004] In the existing technology, strategies such as adding element doping (forming a nano-mesh structure) or heterogeneous composites (such as introducing a graphene interface) are used to inhibit ion migration. For example, Fe doping can form a nano-mesh spinodal structure, which limits the long-range migration of copper ions through the pinning effect, while retaining short-range liquid-like properties to maintain low thermal conductivity (metal elements Fe or Ni as dopants can easily form a nano-network structure and improve thermal stability); Bi, Sb and other doping enhance phonon scattering through lattice distortion and regulate the band structure to improve electrical conductivity; conductive second phases such as graphene and carbon nanotubes are introduced to form a heterogeneous interface to enhance carrier transfer efficiency. Although traditional cuprous sulfide modifiers can improve thermal transport properties, they also produce some side effects. For example, the oxidation of doping elements leads to the introduction of impurity oxides, or the compound's high-temperature structure is unstable, resulting in structural failure during use, and the service temperature and operating conditions exceed the compound's allowable range. In addition, doping elements or carbon atoms react chemically with sulfur to form substances that are detrimental to heat-to-electricity transport, thereby destroying heat-to-electricity conversion. Or some modifiers introduce defects such as grain boundaries, dislocations, and vacancies during the thermoelectric conversion process, reducing thermal conductivity, but the thermoelectric transport properties are not significantly improved, and the thermoelectric conversion performance is less than ideal.

[0005] Therefore, it is necessary to provide an improved technical solution to the above-mentioned deficiencies in the prior art. Summary of the Invention

[0006] The object of the present invention is to provide a light rare earth sulfide modified cuprous sulfide thermoelectric material, a preparation method and its application and a hot pressing sintering mold, so as to help solve or improve the problem of poor thermoelectric conversion effect of cuprous sulfide thermoelectric material.

[0007] In order to achieve the above-mentioned object, the present invention provides the following technical solution: a preparation method of a light rare earth sulfide modified cuprous sulfide thermoelectric material, comprising the following steps: (1) crushing light rare earth sulfide, then adding cuprous sulfide powder, mixing and crushing, and sieving to obtain a solid mixture; (2) cold pressing the solid mixture to obtain a molded material block; (3) placing the molded material block in a hot pressing and sintering mold, and applying pre-pressure to the molded material block to obtain an assembled mold material block; (4) placing the assembled mold material block in a quartz tube of a tube furnace, performing hot pressing and sintering in an inert atmosphere, and cooling to obtain the light rare earth sulfide modified cuprous sulfide thermoelectric material.

[0008] Preferably, the molar ratio of the light rare earth sulfide to cuprous sulfide is (0.001-0.1):1; the light rare earth sulfide is at least one of La2S3, Ce2S3, Pr2S3, Nd2S3, Sm2S3, Y2S3 and EuS.

[0009] Preferably, the hot pressing sintering temperature is 350-750° C., and the holding time is 0.2-18 h; and the cooling is furnace cooling or cooling at a rate of 5-10 K / h.

[0010] Preferably, in step (1), the particle size of the solid mixture is ≤50 μm.

[0011] Preferably, in step (1), the particle size of the solid mixture is ≤10 μm.

[0012] Preferably, in step (1), the particle size of the solid mixture is ≤5 μm.

[0013] Preferably, in step (2), the cold pressing pressure is 2-15 MPa, and the holding time is 1-300 min.

[0014] Preferably, double-sided pressurization is adopted during the cold pressing process; after the molding block is taken out from the cold pressing mold, the step of placing it under inert atmosphere for 3-72 hours is also included.

[0015] Preferably, in step (3), the pre-pressure is 1.5-40 MPa; and before the hot pressing sintering treatment, the process further includes allowing the assembled mold block to stand for 1-12 hours under inert atmosphere.

[0016] The present invention also provides a light rare earth sulfide modified cuprous sulfide thermoelectric material, which adopts the following technical solution: a light rare earth sulfide modified cuprous sulfide thermoelectric material, wherein the light rare earth sulfide modified cuprous sulfide thermoelectric material is prepared by the method described above.

[0017] The present invention also provides a thermoelectric device, which adopts the following technical solution: a thermoelectric device, wherein the thermoelectric device adopts the light rare earth sulfide modified cuprous sulfide thermoelectric material as described above.

[0018] Preferably, the thermoelectric device is a thermoelectric power generation device or a thermoelectric refrigeration device.

[0019] The present invention also provides a hot pressing and sintering mold, which has an inner cavity and at least one opening, a pressure piece is provided through the opening, the inner cavity is used to accommodate the molding block, and the pressure piece is used to apply pre-pressure to the molding block.

[0020] Preferably, there are two openings, and the two openings are symmetrically arranged relative to the molding block.

[0021] More preferably, the pressure member is threadedly connected to the inner cavity of the hot pressing and sintering mold.

[0022] Preferably, the inner cavity of the hot pressing and sintering mold is also equipped with an anti-diffusion gasket and / or an isolation cylindrical ring; the anti-diffusion gasket is arranged between the pressure member and the molding block; and / or the isolation cylindrical ring is arranged between the inner wall of the hot pressing and sintering mold and the molding block.

[0023] Preferably, two anti-diffusion gaskets are provided, and the two anti-diffusion gaskets are respectively provided at two ends of the molding block in the axial direction; and / or the isolation cylindrical ring is provided along the circumference of the molding block.

[0024] More preferably, the anti-diffusion gasket is a graphite paper disc; and / or the isolation cylindrical ring is made of cemented carbide.

[0025] Beneficial effects:

[0026] The present invention uses light rare earth sulfide to modify cuprous sulfide. Light rare earth sulfide has the localized characteristics of the 4f electron layer of rare earth elements, and at the same time has a high melting point and good electrical conductivity. As a sulfide, rare earth ions can be solid-dissolved in cuprous sulfide and can form a heterojunction interface with cuprous sulfide through molecules. It has both thermal stability and thermoelectric transport characteristics, and has better comprehensive performance.

[0027] The preparation method of the light rare earth sulfide modified cuprous sulfide thermoelectric material of the present invention also has the following advantages: (1) light rare earth element resources are abundant and the raw material price is low; (2) the preparation process is simple and can be mass-produced; (3) in terms of the performance of the final product, it is suitable for medium and high temperature temperature difference conversion environments (300-500°C), has low thermal conductivity, and improves the thermoelectric conversion performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The drawings and the accompanying drawings, which constitute part of this application, are intended to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are intended to explain the present invention and do not constitute an undue limitation of the present invention. Among them:

[0029] Figure 1 This is the XRD pattern of the La2S3 / Cu2S sintered block of Example 1 of the present invention;

[0030] Figure 2 The SEM and EDS images of the La2S3 / Cu2S sintered block of Example 1 of the present invention are shown;

[0031] Figure 3 This is the XRD pattern of the Ce2S3 / Cu2S sintered block of Example 2 of the present invention;

[0032] Figure 4 The SEM and EDS images of the Ce2S3 / Cu2S sintered block of Example 2 of the present invention are shown;

[0033] Figure 5 TG-DTA diagram of the Ce2S3 / Cu2S sintered block of Example 2 of the present invention;

[0034] Figure 6 This is an optical photograph of the Pr2S3 / Cu2S sintered block of Example 4 of the present invention;

[0035] Figure 7 This is the XRD pattern of the Pr2S3 / Cu2S sintered block of Example 4 of the present invention;

[0036] Figure 8 The SEM and EDS images of the Pr2S3 / Cu2S sintered block of Example 4 of the present invention;

[0037] Figure 9 This is the XRD pattern of the Nd2S3 / Cu2S sintered block of Example 5 of the present invention;

[0038] Figure 10 The SEM and EDS images of the Nd2S3 / Cu2S sintered block of Example 5 of the present invention are shown;

[0039] Figure 11 This is the XRD pattern of the Sm2S3 / Cu2S sintered block of Example 6 of the present invention;

[0040] Figure 12 The SEM and EDS images of the Sm2S3 / Cu2S sintered block of Example 6 of the present invention are shown;

[0041] Figure 13 This is the XRD pattern of the EuS / Cu2S sintered block of Example 7 of the present invention;

[0042] Figure 14 The SEM and EDS images of the EuS / Cu2S sintered block of Example 7 of the present invention are shown;

[0043] Figure 15 This is an optical photograph of the Cu2S sintered block of Comparative Example 1 of the present invention;

[0044] Figure 16 This is an optical photograph of the Sb2S3 / Cu2S sintered block of Comparative Example 2 of the present invention;

[0045] Figure 17 The SEM and EDS images of the Sb2S3 / Cu2S sintered block of Comparative Example 2 of the present invention are shown;

[0046] Figure 18 This is an optical photograph of the Sm2S3 / Cu2S sintered block of Comparative Example 3 of the present invention;

[0047] Figure 19 This is an optical photograph of the EuS / Cu2S sintered block of Comparative Example 4 of the present invention;

[0048] Figure 20 A flow chart of a method for preparing a light rare earth sulfide modified cuprous sulfide thermoelectric material provided by one embodiment of the present invention;

[0049] Figure 21 A schematic cross-sectional view of a hot pressing and sintering mold provided in one embodiment of the present invention.

[0050] Figure numerals: 1 - mold cavity; 2 - pressure piece; 3 - anti-diffusion gasket; 4 - molding block. DETAILED DESCRIPTION

[0051] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention are within the scope of protection of the present invention.

[0052] The present invention will be described in detail below with reference to the embodiments. It should be noted that the embodiments and features of the embodiments of the present invention can be combined with each other without conflict.

[0053] The present invention addresses the problem that current cuprous sulfide thermoelectric materials have poor thermoelectric conversion effects (for example, cuprous sulfide thermoelectric materials have copper ion segregation or insufficient thermal stability or poor thermoelectric transport properties), and provides a method for preparing light rare earth sulfide modified cuprous sulfide thermoelectric materials.

[0054] The preparation method of the light rare earth sulfide modified cuprous sulfide thermoelectric material of the embodiment of the present invention comprises the following steps: (1) crushing light rare earth sulfide (abbreviated as Ln2S3), then adding cuprous sulfide powder, mixing and crushing, and sieving to obtain a solid mixture; (2) cold pressing the solid mixture to obtain a molded material block; (3) placing the molded material block in a hot pressing sintering mold, and applying pre-pressure to the molded material block to obtain an assembled mold material block; (4) placing the assembled mold material block in a quartz tube of a tube furnace, performing hot pressing sintering in an inert atmosphere, and cooling to obtain the light rare earth sulfide modified cuprous sulfide thermoelectric material.

[0055] This invention uses light rare earth sulfides to modify cuprous sulfide. Light rare earth sulfides (such as La2S3, Ce2S3, and Nd2S3) have excellent chemical stability and unique electronic structure properties, and can improve the performance of the base material (cuprous sulfide) through lattice matching and ion exchange mechanisms. Combining light rare earth sulfides with cuprous sulfide is expected to optimize the thermoelectric properties of cuprous sulfide through a synergistic effect, while also inhibiting copper ion segregation and improving the thermal stability of the material.

[0056] Specifically, light rare earth sulfides have the localized characteristics of the 4f electron layer of rare earth elements, and at the same time have the advantages of high melting point and good conductivity; in addition, light rare earth sulfides and cuprous sulfide are both sulfides, which can not only make light rare earth ions solid-dissolve in cuprous sulfide, but also form a heterojunction interface with cuprous sulfide in molecular form, and have both thermal stability and thermoelectric transport properties, and better overall performance.

[0057] In addition, the present invention performs hot pressing sintering of the molded material block while applying pre-pressure to the molded material block. On the one hand, it can promote the rapid densification of the light rare earth sulfide-modified cuprous sulfide and ensure low resistivity; on the other hand, it can also reduce the reaction temperature and promote the diffusion of light rare earth ions in the cuprous sulfide matrix (which helps to shorten the sintering time to a certain extent), saving resources and energy consumption. At the same time, the addition of light rare earth sulfide does not affect the ion transport characteristics and crystal structure of cuprous sulfide.

[0058] The preparation method of the light rare earth sulfide modified cuprous sulfide thermoelectric material of the present invention also has the following advantages: (1) light rare earth element resources are abundant and the raw material price is low; (2) the preparation process is simple and can be mass-produced; (3) the performance of the final product prepared by the method of the present invention is suitable for medium and high temperature temperature difference conversion environments, the thermal stability is improved, and the thermoelectric conversion performance can be effectively improved.

[0059] In a preferred embodiment of the method for preparing a light rare earth sulfide-modified cuprous sulfide thermoelectric material of the present invention, the molar ratio of light rare earth sulfide to cuprous sulfide is (0.001-0.1):1 (e.g., 0.001:1, 0.003:1, 0.005:1, 0.007:1, 0.009:1, 0.01:1, 0.03:1, 0.05:1, 0.08:1, or 0.1:1); the light rare earth sulfide is at least one of La2S3, Ce2S3, Pr2S3, Nd2S3, Sm2S3, Y2S3, and EuS. If the amount of light rare earth sulfide used is too small, Cu precipitation cannot be effectively suppressed; if the amount of light rare earth sulfide used is too large, costs will increase.

[0060] Preferably, the molar ratio of light rare earth sulfide to cuprous sulfide is 0.006-0.07 (e.g., 0.006, 0.008, 0.01, 0.02, 0.04, 0.06, or 0.07).

[0061] In a preferred embodiment of the method for preparing the light rare earth sulfide modified cuprous sulfide thermoelectric material of the present invention, the hot pressing sintering temperature is 350-750°C (e.g., 350°C, 450°C, 550°C, 650°C, or 750°C), and the holding time is 0.2-18 hours (e.g., 0.2 hours, 0.5 hours, 1 hour, 5 hours, 10 hours, 15 hours, or 18 hours); and the cooling is furnace cooling or cooling at a rate of 5-10K / h (e.g., 5K / h, 6K / h, 7K / h, 8K / h, 9K / h, or 10K / h). If the hot pressing sintering temperature is too high, sulfur loss increases, causing the sulfur vapor pressure in the mold to rise, posing a safety hazard. If the hot pressing sintering temperature is too low, the activation energy of the copper ions in the cuprous sulfide is low, which is not conducive to copper ion diffusion and affects doping uniformity. The holding time of hot pressing sintering mainly affects the doping uniformity. At the appropriate temperature, the diffusion of a certain mass of sample requires a process. Preferably, laboratory samples are generally sintered for 6-12 hours. If the holding time of hot pressing sintering is too short, sintering can still be achieved, but there may be problems with poor local microscopic uniformity. If the holding time of hot pressing sintering is too long, sulfur atoms will be lost, affecting the actual sulfur content and, in turn, the final actual stoichiometric ratio of the product.

[0062] In a preferred embodiment of the method for preparing the light rare earth sulfide modified cuprous sulfide thermoelectric material of the present invention, in step (1), the particle size of the solid mixture is ≤50 μm. Excessively large particle size may reduce grain boundaries (reduced grain boundaries may reduce the energy filtering effect, resulting in a lower Seebeck coefficient), reduce carrier scattering, and lead to a decrease in resistivity. At the same time, large particle size may reduce the optimization of the energy level structure at the interface, affecting carrier concentration and diffusion, and reducing the Seebeck coefficient. Furthermore, reduced grain boundaries and interfaces will reduce phonon scattering, leading to an increase in lattice thermal conductivity. Large particle size may also lead to a loose material structure and cracks, affecting material stability and performance in practical applications. Negative effects of too small particle size may include: structural damage and performance degradation, reduced electrical conductivity, increased difficulty and cost in preparation, deterioration of mechanical properties, and adverse changes in thermal conductivity.

[0063] Preferably, in step (1), the particle size of the solid mixture is ≤10 μm.

[0064] More preferably, in step (1), the particle size of the solid mixture is ≤5 μm.

[0065] Further preferably, in step (1), the particle size of the solid mixture is 1-5 μm.

[0066] In a preferred embodiment of the preparation method of the light rare earth sulfide modified cuprous sulfide thermoelectric material of the present invention, in step (2), the pressure of cold pressing is 2-15MPa (for example, 2MPa, 5MPa, 8MPa, 10MPa, 12MPa or 15MPa), and the holding time is 1-300min (for example, 1min, 5min, 10min, 50min, 100min, 150min, 200min, 250min or 300min). Among them, the pressure of cold pressing will affect the density of the obtained molded material block; the greater the pressure, the higher the density, but the greater the mold loss; low pressure will lead to poor sample density. During cold pressing, the pressurization process requires buffering, so the minimum holding time is 1min. The longer the time, the denser the powder is pressed. In actual industrial production, the time of the automated tablet press is also very short and efficient, generally not exceeding 3min; if the holding time is too long, the density difference of the molded material block is not obvious.

[0067] In a preferred embodiment of the method for preparing the light rare earth sulfide-modified cuprous sulfide thermoelectric material of the present invention, double-sided pressurization is employed during cold pressing. After the molded block is removed from the cold pressing mold, the method further includes placing the molded block under an inert atmosphere for a period of 3-72 hours (e.g., 3 hours, 10 hours, 20 hours, 30 hours, 40 hours, 50 hours, 60 hours, or 72 hours). This placement of the molded block under an inert atmosphere after removal from the cold pressing mold helps to release internal stress during the cold pressing process and prevent cracking after sintering. Furthermore, the inert atmosphere helps prevent sample oxidation; omitting this step may increase the probability of cracking after sintering.

[0068] In a preferred embodiment of the method for preparing the light rare earth sulfide modified cuprous sulfide thermoelectric material of the present invention, in step (3), the pre-pressure is 1.5-40 MPa (for example, 1.5 MPa, 5 MPa, 10 MPa, 15 MPa, 20 MPa, 25 MPa, 30 MPa, 35 MPa, or 40 MPa); and before the hot pressing sintering process, the method further includes the step of allowing the assembled mold block to stand for 1-12 hours (for example, 1 hour, 3 hours, 6 hours, 9 hours, or 12 hours) under inert atmosphere. Excessive pre-pressure will crush the molded block; too little pre-pressure will affect the sealing of the mold and the density of the final sintered product (too little pre-pressure may cause volatilization of gaseous sulfur vapor at high temperature, thereby affecting the density of the product). The reason why the assembled mold block is left to stand for a period of time under the protection of an inert atmosphere before hot pressing and sintering is that: after the pre-pressure is applied, there is still internal stress in the sample, and this step can release the internal stress. Omitting this step will increase the probability of cracking of the molded block.

[0069] In a preferred embodiment of the method for preparing the light rare earth sulfide modified cuprous sulfide thermoelectric material of the present invention, in step (1), pulverization is performed by wet ball milling; after the mixed pulverization, the step further includes removing the solvent of the wet ball milling.

[0070] Preferably, in step (1), when the light rare earth sulfide is wet ball milled, the ball-to-material ratio is (5-25):1 (e.g., 5:1, 10:1, 15:1, 20:1, or 25:1), and the ball milling time is 1-12 hours (e.g., 1 hour, 3 hours, 6 hours, 9 hours, or 12 hours). More preferably, the solvent for wet ball milling is anhydrous ethanol.

[0071] Preferably, after adding cuprous sulfide and mixing and crushing, heating and slowly stirring until the solvent is completely volatilized to obtain a solid mixture, and then the solid mixture is sieved.

[0072] The present invention also provides a light rare earth sulfide modified cuprous sulfide thermoelectric material. The light rare earth sulfide modified cuprous sulfide thermoelectric material of the embodiment of the present invention is prepared by the method described above.

[0073] The present invention also provides a thermoelectric device. The thermoelectric device of an embodiment of the present invention uses the light rare earth sulfide modified cuprous sulfide thermoelectric material as described above (the light rare earth sulfide modified cuprous sulfide thermoelectric material of the present invention can be used to manufacture thermoelectric devices).

[0074] Preferably, the thermoelectric device is a thermoelectric power generation device or a thermoelectric refrigeration device.

[0075] The present invention also proposes a hot pressing sintering mold, such as Figure 21 As shown, the hot pressing and sintering mold of the embodiment of the present invention has an inner cavity 1 (the hot pressing mold body can be a hollow columnar structure; for example, a hollow hexagonal columnar structure) and at least one opening, through which a pressure member 2 is provided. The inner cavity 1 is used to accommodate the molding block 4, and the pressure member 2 is used to apply pre-pressure to the molding block 4. The provision of the pressure member 2 enables hot pressing and sintering of the molding block under pressure.

[0076] The hot pressing and sintering mold can be used for preparing the light rare earth sulfide modified cuprous sulfide thermoelectric material of the present invention.

[0077] Preferably, there are two openings, and the two openings are symmetrically arranged relative to the molding block 4 .

[0078] More preferably, the pressure member 2 is threadedly connected to the inner cavity of the hot pressing and sintering mold (preferably, the pressure member 2 is a bolt). By threading the pressure member 2 to the inner cavity of the hot pressing and sintering mold, it is convenient to drive the pressure member 2 to move away from or toward the forming block 4 to achieve pressure applied by the pressure member 2 to the forming block 4. For example, when the pressure member 2 is a bolt, a long torque wrench can be used to adjust the bolt so that the bolt moves toward the forming block 4, thereby applying pre-pressure to the forming block 4.

[0079] In a preferred embodiment of the hot-pressing and sintering mold of the present invention, an anti-diffusion gasket 3 and / or an isolating cylindrical ring (not shown) are further installed in the inner cavity 1 of the hot-pressing and sintering mold; the anti-diffusion gasket 3 is disposed between the pressure member 2 and the molding block 4; and / or the isolating cylindrical ring is disposed between the inner wall of the hot-pressing and sintering mold and the molding block 4 (sufficiently to prevent direct contact between the molding block and the inner wall of the hot-pressing and sintering mold). The anti-diffusion gasket 3 and the isolating cylindrical ring can prevent contamination of the molding block 4 during the hot-pressing process.

[0080] In a preferred embodiment of the hot pressing sintering mold of the present invention, two anti-diffusion gaskets 3 are provided, and the two anti-diffusion gaskets 3 are respectively arranged at both ends of the molding block 4 in the axial direction; and / or, an isolation cylindrical ring is arranged along the circumference of the molding block.

[0081] In a preferred embodiment of the hot pressing sintering mold of the present invention, the anti-diffusion gasket 3 is a graphite paper disc; and / or the isolation cylindrical ring is made of cemented carbide.

[0082] Preferably, the thickness of the graphite paper disc is 1 mm.

[0083] The light rare earth sulfide modified cuprous sulfide thermoelectric material of the present invention, its preparation method and application are described in detail below through specific examples.

[0084] Unless otherwise specified, the raw materials used in the following examples can be purchased commercially; for example, the sources of the main raw materials are as follows:

[0085] Material purity Molecular weight (g / mol) Manufacturer <![CDATA[Cu2S]]> 99% 159.16 Guangdong Yuanfeng Chemical Technology Co., Ltd. <![CDATA[Ce2S3]]> 99% 344.08 Nanyang Xinyu New Material Technology Co., Ltd. EuS 99% 184.04 Nanyang Xinyu New Material Technology Co., Ltd. <![CDATA[La2S3]]> 99% 374.01 Nanyang Xinyu New Material Technology Co., Ltd. <![CDATA[Nd2S3]]> 99% 384.68 Nanyang Xinyu New Material Technology Co., Ltd. <![CDATA[Sm2S3]]> 99% 396.89 Nanyang Xinyu New Material Technology Co., Ltd. <![CDATA[Pr2S3]]> 99% 378.01 Nanyang Xinyu New Material Technology Co., Ltd.

[0086] Example 1

[0087] The preparation method of the light rare earth sulfide modified cuprous sulfide thermoelectric material of this embodiment comprises the following steps (refer to Figure 20 ):

[0088] (1) Weigh 0.75 g of La2S3 coarse particles and add them to a stainless steel ball mill. Then weigh 50 g of stainless steel balls and add them to the ball mill. Add 150 mL of organic solvent (anhydrous ethanol). Then seal the ball mill with a sealing gasket and fix it on a planetary ball mill. Set the ball milling parameters: speed 2400 r / min, ball milling for 72 h, and adjust the forward and reverse directions every 10 minutes. After the ball milling is completed, weigh 9.25 g of Cu2S and add it to the slurry formed by the above mixture (first homogenization). Then set the speed to 300 r / min and ball mill for 3 h.

[0089] Heating and screening: After the ball milling is completed, the above slurry (second homogenous mixture) and the steel balls are transferred to a constant temperature oil bath pot, the temperature is set to 80°C, and the anhydrous ethanol is evaporated by slow stirring. Then, the obtained solid mixture is sieved through a 200-mesh sieve to obtain an initial mixture (most of the La2S3 in the initial mixture has a particle size of 1-2 μm, and most of the Cu2S has a particle size of 3-5 μm).

[0090] (2) Weigh 2 g of the initial mixture of La2S3 and Cu2S and place it in a cemented carbide mold (cold pressing mold) and use double-sided pressure cold pressing to form it. The cold pressing pressure is 3 MPa; the holding time is 5 minutes to obtain a molded block (cold pressed block); after the molded block is taken out of the cold pressing mold, it is placed under inert atmosphere for 12 hours.

[0091] (3) Assemble two 1 mm thick graphite paper discs (anti-diffusion gaskets) and a carbide isolation cylindrical ring in a high-temperature resistant hot pressing sintering mold (the two graphite paper original sheets are respectively located between the molding block and the bolts, and the carbide isolation cylindrical ring is located in the circumference of the molding block to prevent the molding block from direct contact with the hot pressing sintering mold). Then, apply a pre-pressure of 5 MPa to the molding block through two bolts (pressure pieces), and let the assembled mold block stand for 12 hours under the protection of an inert atmosphere.

[0092] (4) The assembled mold block is placed in a quartz tube of a tubular furnace, and is hot-pressed and sintered under inert atmosphere protection by first evacuating the vacuum and then introducing argon inert gas: the hot-pressing sintering temperature is 400°C and the holding time is 12 hours; the cooling step is cooling with the furnace, and then the mold is disassembled to obtain the light rare earth sulfide modified cuprous sulfide thermoelectric material (La2S3 / Cu2S sintered block) of this embodiment.

[0093] The sintered block was surface ground, polished and cut to obtain La2S3 / Cu2S test blocks for performance testing and analysis.

[0094] Characterization Test

[0095] The surface morphology of the La2S3 / Cu2S test block was observed and analyzed using an optical microscope, mainly analyzing the precipitation of copper ions. The main parameters of the XRD test of the La2S3 / Cu2S test block are: Cu target K α The La2S3 / Cu2S test piece was observed using a scanning electron microscope (SEM) with a voltage of 40 kV, a current of 20 mA, a scanning step size of 0.02°, and a scanning speed of 6° / min. The phase composition was confirmed by comparing the diffraction peaks with those of an orthorhombic Cu2S standard card (JCPDS#33-0490). The micromorphology, grain size, and elemental distribution of the La2S3 / Cu2S test piece were also observed using a scanning electron microscope.

[0096] The mixed powder (mixed powder obtained by grinding La2S3 / Cu2S sintered blocks; general test powder for thermal analysis) was weighed and placed in a dry corundum crucible. The TG / DTA analyzer (NETZSCHSTA 449C, NETZSCH Thermogravimetric analysis was performed at the La2S3 / Cu2S test block using a thermoelectric transport measurement system to simultaneously measure the Seebeck coefficient (S), electrical conductivity (σ), and carrier concentration.

[0097] After thermal analysis and electrical transport performance tests, the test results show that the La2S3 / Cu2S sintered block prepared in this embodiment can be used as a thermoelectric material, and the thermal stability temperature and electrical performance parameters are shown in Table 1 below.

[0098] Figure 1 XRD pattern of the La2S3 / Cu2S sintered block prepared in this example; Figure 2 These are the SEM and EDS images of the La2S3 / Cu2S sintered block prepared in this example.

[0099] Figure 1 In the figure, the XRD pattern of the La2S3 / Cu2S sintered block is the same as the PDF card pattern of Cu2S, indicating that the crystal form of the product remains unchanged after the addition of La2S3; Figure 2 The SEM and EDS images of the La2S3 / Cu2S sintered block show that after the addition of La2S3, the La element is evenly distributed in the Cu2S matrix, forming a pinning effect.

[0100] Example 2

[0101] The preparation method of the light rare earth sulfide modified cuprous sulfide thermoelectric material of this embodiment includes the following steps:

[0102] (1) Weigh 0.6 g of Ce2S3 coarse particles and add them to a stainless steel ball mill. Then weigh 12 g of stainless steel balls and add them to the ball mill. Add 120 mL of anhydrous ethanol, seal the ball mill with a sealing gasket, and fix it on a planetary ball mill. Set the ball milling parameters: speed 600 r / min, ball milling for 24 h, and adjust the forward and reverse directions every 10 minutes. After the ball milling is completed, weigh 9.4 g of Cu2S and add it to the slurry formed by the above mixture. Then set the speed to 300 r / min and ball mill for 3 h.

[0103] After ball milling, the slurry and steel balls are transferred to a constant temperature oil bath pot, the temperature is set to 80 ° C, and the anhydrous ethanol is evaporated by slow stirring. Then, the obtained solid mixture is sieved through a 200-mesh sieve to obtain an initial mixture (most of the Ce2S3 in the initial mixture has a particle size of 1-2 μm, and most of the Cu2S has a particle size of 3-5 μm).

[0104] (2) Weigh 2 g of the initial mixture of Ce2S3 and Cu2S and place it in a cemented carbide mold (cold pressing mold) and use double-sided pressure cold pressing to form the mixture. The cold pressing pressure is 3 MPa. The holding time is 5 minutes to obtain a molded block. After the molded block is taken out of the cold pressing mold, it is placed under inert atmosphere for 4 hours.

[0105] (3) (anti-diffusion gasket) and carbide isolation cylindrical ring are assembled in a high-temperature resistant hot pressing sintering mold (the two graphite paper original sheets are respectively located between the molding block and the bolts, and the carbide isolation cylindrical ring is located in the circumference of the molding block to prevent the molding block from directly contacting the hot pressing sintering mold). Then, a pre-pressure of 5 MPa is applied to the molding block through two bolts (pressure pieces), and the assembled mold block is left to stand for 3 hours under the protection of an inert atmosphere.

[0106] (4) After assembly, the mold block is placed in a quartz tube of a tubular furnace, and is hot-pressed and sintered under the protection of an argon inert atmosphere by first evacuating the vacuum and then introducing an inert gas: the hot-pressing sintering temperature is 400°C, and the holding time is 6 hours; the cooling step is cooling with the furnace, and then the mold is disassembled to obtain the light rare earth sulfide modified cuprous sulfide thermoelectric material (Ce2S3 / Cu2S sintered block) of this embodiment.

[0107] The sintered block was surface ground, polished and cut to obtain a Ce2S3 / Cu2S test block for performance testing and analysis.

[0108] Characterization Test

[0109] The surface morphology of Ce2S3 / Cu2S sintered blocks was observed and analyzed using an optical microscope, mainly analyzing the precipitation of copper ions. The main parameters of XRD test of Ce2S3 / Cu2S test blocks are: Cu target K α The line was operated at 40 kV, 20 mA, a scan step size of 0.02°, and a scan speed of 6° / min. The phase composition was confirmed by comparing the diffraction peaks with those of an orthorhombic Cu2S standard card (JCPDS#33-0490). The micromorphology, grain size, and elemental distribution of the Ce2S3 / Cu2S test piece were observed using a scanning electron microscope.

[0110] The mixed powder was weighed and placed in a dry corundum crucible and analyzed using a TG / DTA analyzer (NETZSCH STA449C, NETZSCH Thermogravimetric analysis was performed at the company's facility in Berlin, Germany; the entire heating and cooling process was conducted in a nitrogen atmosphere. The thermoelectric performance of the Ce2S3 / Cu2S test piece was measured using a Seebeck coefficient / resistance measurement system to simultaneously measure the Seebeck coefficient (S), electrical conductivity (σ), and carrier concentration.

[0111] After thermal analysis and electrical transport performance tests, the test results show that the Ce2S3 / Cu2S sintered block prepared in this embodiment can be used as a thermoelectric material, and the thermal stability temperature and electrical performance parameters are shown in Table 1 below.

[0112] Figure 3 is the XRD pattern of the Ce2S3 / Cu2S sintered block prepared in this example; Figure 4 These are the SEM and EDS images of the Ce2S3 / Cu2S sintered block prepared in this example. Figure 5 This is the thermal analysis TG-DTA diagram of the Ce2S3 / Cu2S sintered block prepared in this example.

[0113] Figure 3In the figure, the XRD pattern of Ce2S3 / Cu2S sintered block is the same as the PDF card pattern of Cu2S, indicating that the crystal form of the product remains unchanged after adding Ce2S3; Figure 4 The SEM and EDS images of the Ce2S3 / Cu2S sintered block show that after adding Ce2S3, the Ce element is evenly distributed in the Cu2S matrix, forming a pinning effect. Figure 5 It can be seen that the thermal stability of Ce2S3 / Cu2S sintered blocks is significantly improved.

[0114] Example 3

[0115] The preparation method of the light rare earth sulfide modified cuprous sulfide thermoelectric material of this embodiment includes the following steps:

[0116] (1) Weigh 0.7 g of Ce2S3 coarse particles and add them to a stainless steel ball mill. Then weigh 12 g of stainless steel balls and add them to the ball mill. Add 120 mL of anhydrous ethanol, seal the ball mill with a sealing gasket, and fix it on a planetary ball mill. Set the ball milling parameters: speed 600 r / min, ball milling for 24 h, and adjust the forward and reverse directions every 10 minutes. After the ball milling is completed, weigh 9.3 g of Cu2S and add it to the slurry formed by the above mixture. Then set the speed to 300 r / min and ball mill for 3 h.

[0117] After ball milling, the slurry and steel balls are transferred to a constant temperature oil bath pot, the temperature is set to 80 ° C, and the anhydrous ethanol is evaporated by slow stirring. Then, the obtained solid mixture is sieved through a 200-mesh sieve to obtain an initial mixture (most of the Ce2S3 in the initial mixture has a particle size of 1-2 μm, and most of the Cu2S has a particle size of 3-5 μm).

[0118] (2) Weigh 2 g of the initial mixture of Ce2S3 and Cu2S and place it in a cemented carbide mold using double-sided pressure cold pressing. The cold pressing pressure is 5 MPa and the pressure holding time is 15 minutes. The mixture molded block is taken out of the cold pressing mold and placed under inert atmosphere for 5 hours.

[0119] (3) Two 1 mm thick graphite paper discs and a carbide isolation cylindrical ring were assembled in a high-temperature mold, and then a preload of 5 MPa was applied through two bolts. After assembly, the mold block was left to stand for 4 hours under inert atmosphere protection.

[0120] (4) After assembly, the mold block is placed in a quartz tube of a tubular furnace, and is first vacuumed and then introduced with argon inert gas, and hot-pressed sintering is performed under the protection of an inert atmosphere: the hot-pressing sintering temperature is 600°C, and the holding time is 12 hours; the cooling step is cooling with the furnace, and then the mold is disassembled to obtain the light rare earth sulfide modified cuprous sulfide thermoelectric material (Ce2S3 / Cu2S sintered block) of this embodiment.

[0121] The sintered block was surface ground, polished and cut to obtain a Ce2S3 / Cu2S test block for performance testing and analysis.

[0122] There is little difference in the microscopic morphology of the Ce2S3 / Cu2S sintered blocks prepared in Example 3 and Example 2.

[0123] After thermal analysis and electrical transport performance tests, the Ce2S3 / Cu2S sintered block prepared in this embodiment was obtained as a thermoelectric material, and the thermal stability temperature and electrical performance parameters are shown in Table 1 below.

[0124] Example 4

[0125] The preparation method of the light rare earth sulfide modified cuprous sulfide thermoelectric material of this embodiment includes the following steps:

[0126] (1) Weigh 0.8 g of Pr2S3 coarse particles and add them to a stainless steel ball mill. Then weigh 16 g of stainless steel balls and add them to the ball mill. Add 120 mL of anhydrous ethanol, seal the ball mill with a sealing gasket, and fix it on a planetary ball mill. Set the ball milling parameters: speed 500 r / min, ball milling for 8 h, and adjust the forward and reverse directions every 8 minutes. After the ball milling is completed, weigh 9.2 g of Cu2S and add it to the slurry formed by the above mixture. Then set the speed to 550 r / min and ball mill for 2 h.

[0127] After the ball milling is completed, the above slurry and steel balls are transferred to a constant temperature oil bath pot, the temperature is set to 80°C, and the anhydrous ethanol is evaporated by slow stirring. Then, the obtained solid mixture is sieved with a 200-mesh sieve to obtain an initial mixture (the particle size of most Pr2S3 in the initial mixture is 1-2 μm, and the particle size of most Cu2S is 3-5 μm).

[0128] (2) Weigh 2 g of the initial mixture of Pr2S3 and Cu2S and place it in a cemented carbide mold (cold pressing mold) and use double-sided pressure cold pressing to form the mixture. The cold pressing pressure is 4 MPa; the pressure is maintained for 3 minutes to obtain a molded block; after the molded block is taken out of the cold pressing mold, it is placed under inert atmosphere for 2 hours.

[0129] (3) Assemble two 1mm thick graphite paper discs (anti-diffusion gaskets) and a carbide isolation cylindrical ring in a high-temperature resistant hot pressing sintering mold (the two graphite paper original sheets are respectively located between the molding block and the bolts, and the carbide isolation cylindrical ring is located in the circumference of the molding block to prevent the molding block from directly contacting the hot pressing sintering mold). Then, apply a preload of 5MPa through the two bolts, and let the assembled mold block stand for 6 hours under the protection of an inert atmosphere.

[0130] (4) The assembled mold block is placed in a quartz tube of a tubular furnace, and is hot-pressed and sintered under inert atmosphere protection by first evacuating the vacuum and then introducing an inert gas: the hot-pressing sintering temperature is 500°C and the holding time is 12 hours; the cooling step is cooling with the furnace, and then the mold is disassembled to obtain the light rare earth sulfide modified cuprous sulfide thermoelectric material (Pr2S3 / Cu2S sintered block) of this embodiment.

[0131] The sintered block was surface ground, polished and cut to obtain a Pr2S3 / Cu2S test block for performance testing and analysis.

[0132] Characterization Test

[0133] The surface morphology of the Pr2S3 / Cu2S sintered block was observed and analyzed using an optical microscope, mainly analyzing the precipitation of copper ions. The main parameters of the XRD test of the Pr2S3 / Cu2S test block are: Cu target K α The Pr2S3 / Cu2S test piece was observed using a scanning electron microscope with a voltage of 40 kV, a current of 20 mA, a scanning step size of 0.02°, and a scanning speed of 6° / min. The phase composition was confirmed by comparing the diffraction peaks with those of an orthorhombic Cu2S standard card (JCPDS#33-0490). The micromorphology, grain size, and elemental distribution of the Pr2S3 / Cu2S test piece were observed using a scanning electron microscope.

[0134] The mixed powder was weighed and placed in a dry corundum crucible. The TG / DTA analyzer (NETZSCH STA449C, NETZSCH Thermogravimetric analysis was performed at the company's facility in Munich, Germany. The entire heating and cooling process was conducted in a nitrogen atmosphere. The thermoelectric performance of the Pr2S3 / Cu2S test piece was measured using a Seebeck coefficient / resistance measurement system to simultaneously measure the Seebeck coefficient (S), electrical conductivity (σ), and carrier concentration.

[0135] After thermal analysis and electrical transport performance tests, the test results show that the Pr2S3 / Cu2S sintered block prepared in this embodiment can be used as a thermoelectric material, and the thermal stability temperature and electrical performance parameters are shown in Table 1 below.

[0136] Figure 6 This is an optical photograph of the Pr2S3 / Cu2S sintered block prepared in this example; Figure 7 This is the XRD pattern of the Pr2S3 / Cu2S sintered block prepared in this example; Figure 8 This is the SEM image of the Pr2S3 / Cu2S sintered block prepared in this example.

[0137] Figure 6 In the optical photograph of the Pr2S3 / Cu2S sintered block, there is no obvious copper precipitation on the surface, indicating that the addition of Pr2S3 can inhibit the precipitation of copper ions. Figure 7 In the figure, the XRD pattern of the Pr2S3 / Cu2S sintered block is the same as the PDF card pattern of Cu2S, indicating that the crystal form of the product remains unchanged after the addition of Pr2S3. Figure 8 In the figure, the SEM and EDS images of the Pr2S3 / Cu2S sintered block show that after adding Pr2S3, the Pr element is evenly distributed in the Cu2S matrix, forming a pinning effect.

[0138] Example 5

[0139] The preparation method of the light rare earth sulfide modified cuprous sulfide thermoelectric material of this embodiment includes the following steps:

[0140] (1) Weigh 0.7 g of Nd2S3 coarse particles and add them to a stainless steel ball mill. Then weigh 16 g of stainless steel balls and add them to the ball mill. Add 120 mL of anhydrous ethanol, seal the ball mill with a sealing gasket, and fix it on a planetary ball mill. Set the ball milling parameters: speed 500 r / min, ball milling for 6 h, and adjust the forward and reverse directions every 6 minutes. After the ball milling is completed, weigh 19.3 g of Cu2S and add it to the slurry formed by the above mixture. Then set the speed to 450 r / min and ball mill for 6 h.

[0141] After the ball milling is completed, the above slurry and steel balls are transferred to a constant temperature oil bath pot, the temperature is set to 80°C, and the anhydrous ethanol is evaporated by slow stirring. Then, the obtained solid mixture is sieved through a 200-mesh sieve to obtain an initial mixture (most of the Nd2S3 in the initial mixture has a particle size of 1-2 μm, and most of the Cu2S has a particle size of 3-5 μm).

[0142] (2) Weigh 2 g of the initial mixture of Nd2S3 and Cu2S and place it in a cemented carbide mold (cold pressing mold) and use double-sided pressure cold pressing to form the mixture. The cold pressing pressure is 8 MPa; the holding time is 1 minute to obtain a molded block; after the molded block is taken out of the cold pressing mold, it is placed under inert atmosphere for 4 hours.

[0143] (3) Assemble two 1 mm thick graphite paper discs (anti-diffusion gaskets) and a carbide isolation cylindrical ring in a high-temperature resistant hot pressing sintering mold (the two graphite paper original sheets are respectively located between the molding block and the bolts, and the carbide isolation cylindrical ring is located in the circumference of the molding block to prevent the molding block from directly contacting the hot pressing sintering mold). Then, apply a pre-pressure of 5 MPa to the molding block through two bolts (pressure pieces), and let the assembled mold block stand for 4 hours under the protection of an inert atmosphere.

[0144] (4) The assembled mold block is placed in a quartz tube of a tubular furnace, and is hot-pressed and sintered under inert atmosphere protection by first evacuating the vacuum and then introducing argon inert gas: the hot-pressing sintering temperature is 600°C and the holding time is 12 hours; the cooling step is cooling with the furnace, and then the mold is disassembled to obtain the light rare earth sulfide modified cuprous sulfide thermoelectric material (Nd2S3 / Cu2S sintered block) of this embodiment.

[0145] The sintered block was surface ground, polished and cut to obtain Nd2S3 / Cu2S test blocks for performance testing and analysis.

[0146] Characterization Test

[0147] The surface morphology of the Nd2S3 / Cu2S sintered block was observed and analyzed using an optical microscope, mainly analyzing the precipitation of copper ions. The main parameters of the XRD test of the Nd2S3 / Cu2S test block are: Cu target K α The Nd2S3 / Cu2S test piece was tested using a 40 kV line, a 20 mA current, a 0.02° scanning step, and a 6° / min scanning speed. The phase composition was confirmed by comparing the diffraction peaks with an orthorhombic Cu2S standard card (JCPDS#33-0490). The micromorphology, grain size, and elemental distribution of the Nd2S3 / Cu2S test piece were observed using a scanning electron microscope.

[0148] The mixed powder was weighed and placed in a dry corundum crucible and analyzed using a TG / DTA analyzer (NETZSCH STA449C, NETZSCH Thermogravimetric analysis was performed at the Nd2S3 / Cu2S test block using a Seebeck coefficient / resistance measurement system to simultaneously measure the Seebeck coefficient (S), electrical conductivity (σ), and carrier concentration.

[0149] After thermal analysis and electrical transport performance tests, the test results show that the Nd2S3 / Cu2S sintered block prepared in this embodiment can be used as a thermoelectric material, and the thermal stability temperature and electrical performance parameters are shown in Table 1 below.

[0150] Figure 9 is the XRD pattern of the Nd2S3 / Cu2S sintered block prepared in this example; Figure 10 This is the SEM image of the Nd2S3 / Cu2S sintered block prepared in this example.

[0151] Figure 9 In the figure, the XRD pattern of the Nd2S3 / Cu2S sintered block is the same as the PDF card pattern of Cu2S, indicating that the crystal form of the product remains unchanged after the addition of Nd2S3. Figure 10In the figure, the SEM and EDS images of the Nd2S3 / Cu2S sintered block show that after adding Nd2S3, the Nd element is evenly distributed in the Cu2S matrix, forming a pinning effect.

[0152] Example 6

[0153] The preparation method of the light rare earth sulfide modified cuprous sulfide thermoelectric material of this embodiment includes the following steps:

[0154] (1) Weigh 0.3 g of Sm2S3 coarse particles and add them to a stainless steel ball mill. Then weigh 3 g of stainless steel balls and add them to the ball mill. Add 120 mL of anhydrous ethanol, seal the ball mill with a sealing gasket, and fix it on a planetary ball mill. Set the ball milling parameters: speed 350 r / min, ball milling for 3 h, and adjust the forward and reverse directions every 2 minutes. After the ball milling is completed, weigh 19.7 g of Cu2S and add it to the slurry formed by the above mixture. Then set the speed to 250 r / min and ball mill for 8 h.

[0155] After ball milling, the slurry and steel balls are transferred to a constant temperature oil bath pot, the temperature is set to 80 ° C, and the anhydrous ethanol is evaporated by slow stirring. Then, the obtained solid mixture is sieved through a 200-mesh sieve to obtain an initial mixture (the particle size of Sm2S3 in the initial mixture is 1-2 μm, and the particle size of Cu2S is 3-5 μm).

[0156] (2) Weigh 2 g of the initial mixture of Sm2S3 and Cu2S and place it in a cemented carbide mold (cold pressing mold) and use double-sided pressure cold pressing to form the mixture. The cold pressing pressure is 6 MPa. The holding time is 2 minutes to obtain a molded block. After the molded block is taken out of the cold pressing mold, it is placed under inert atmosphere for 2 hours.

[0157] (3) Assemble two 1 mm thick graphite paper discs (anti-diffusion gaskets) and a carbide isolation cylindrical ring in a high-temperature resistant hot pressing sintering mold, and then apply a preload of 5 MPa through two bolts. After assembly, the mold block is left to stand for 2 hours under inert atmosphere protection.

[0158] (4) The assembled mold block is placed in a quartz tube of a tubular furnace, and is hot-pressed and sintered under inert atmosphere protection by first evacuating the vacuum and then introducing argon inert gas: the hot-pressing sintering temperature is 400°C and the holding time is 12 hours; the cooling step is cooling with the furnace, and then the mold is disassembled to obtain the light rare earth sulfide modified cuprous sulfide thermoelectric material (Sm2S3 / Cu2S sintered block) of this embodiment.

[0159] The sintered block was surface ground, polished and cut to obtain Sm2S3 / Cu2S test blocks for performance testing and analysis.

[0160] Characterization Test

[0161] The surface morphology of the Sm2S3 / Cu2S sintered block was observed and analyzed using an optical microscope, mainly analyzing the precipitation of copper ions. The main parameters of the XRD test of the Sm2S3 / Cu2S test block are: Cu target K α The line was operated at 40 kV, 20 mA, a scan step size of 0.02°, and a scan speed of 6° / min. The phase composition was confirmed by comparing the diffraction peaks with an orthorhombic Cu2S standard card (JCPDS#33-0490). The micromorphology, grain size, and elemental distribution of the Sm2S3 / Cu2S test piece were observed using a scanning electron microscope.

[0162] The mixed powder was weighed and placed in a dry corundum crucible and analyzed using a TG / DTA analyzer (NETZSCH STA449C, NETZSCH Thermogravimetric analysis was performed at the Sm2S3 / Cu2S test block using a Seebeck coefficient / resistance measurement system to simultaneously measure the Seebeck coefficient (S), electrical conductivity (σ), and carrier concentration.

[0163] After thermal analysis and electrical transport performance tests, the test results show that the Sm2S3 / Cu2S sintered block prepared in this embodiment is used as a thermoelectric material, and the thermal stability temperature and electrical performance parameters are shown in Table 1 below.

[0164] Figure 11 This is the XRD pattern of the Sm2S3 / Cu2S sintered block prepared in this example; Figure 12 This is the SEM image of the Sm2S3 / Cu2S sintered block prepared in this example.

[0165] Figure 11 In the figure, the XRD pattern of the Sm2S3 / Cu2S sintered block is the same as the PDF card pattern of Cu2S, indicating that the crystal form of the product remains unchanged after the addition of Sm2S3. Figure 12 In the figure, the SEM and EDS images of the Sm2S3 / Cu2S sintered block show that after the addition of Sm2S3, the Sm element is evenly distributed in the Cu2S matrix, forming a pinning effect.

[0166] Example 7

[0167] The preparation method of the light rare earth sulfide modified cuprous sulfide thermoelectric material of this embodiment includes the following steps:

[0168] (1) Weigh 0.7 g of EuS coarse particles and add them to a stainless steel ball mill. Then weigh 8 g of stainless steel balls and add them to the ball mill. Add 120 mL of anhydrous ethanol, seal the ball mill with a sealing gasket, and fix it on a planetary ball mill. Set the ball milling parameters: speed 250 r / min, ball milling for 8 h, and adjust the forward and reverse directions every 2 minutes. After the ball milling is completed, weigh 9.3 g of Cu2S and add it to the slurry formed by the above mixture. Then set the speed to 250 r / min and ball mill for 2 h.

[0169] After the ball milling is completed, the slurry and steel balls are transferred to a constant temperature oil bath pot, the temperature is set to 80°C, and the anhydrous ethanol is evaporated by slow stirring. Then, the obtained solid mixture is sieved through a 200-mesh sieve to obtain an initial mixture (the particle size of most EuS in the initial mixture is 1-2 μm, and the particle size of most Cu2S is 3-5 μm).

[0170] (2) Weigh 2 g of the initial mixture of EuS and Cu2S and place it in a cemented carbide mold (cold pressing mold) and use double-sided pressure cold pressing to form the mixture. The cold pressing pressure is 8 MPa. The holding time is 1 minute to obtain a molded block. After the molded block is removed from the cold pressing mold, it is placed under inert atmosphere for 4 hours.

[0171] (3) Assemble two 1 mm thick graphite paper discs (anti-diffusion gaskets) and a carbide isolation cylindrical ring in a high-temperature resistant hot pressing sintering mold (the two graphite paper original sheets are respectively located between the molding block and the bolts, and the carbide isolation cylindrical ring is located in the circumference of the molding block to prevent the molding block from directly contacting the hot pressing sintering mold). Then, apply a pre-pressure of 3 MPa to the molding block through two bolts (pressure pieces), and let the assembled mold block stand for 4 hours under the protection of an inert atmosphere.

[0172] (4) The assembled mold block is placed in a quartz tube of a tubular furnace, and is hot-pressed and sintered under inert atmosphere protection by first evacuating the vacuum and then introducing argon inert gas: the hot-pressing sintering temperature is 600°C and the holding time is 12 hours; the cooling step is cooling with the furnace, and then the mold is disassembled to obtain the light rare earth sulfide modified cuprous sulfide thermoelectric material (EuS / Cu2S sintered block) of this embodiment.

[0173] The sintered block was surface ground, polished, and cut to obtain a EuS / Cu2S test block for performance testing and analysis.

[0174] Characterization Test

[0175] The surface morphology of the EuS / Cu2S sintered block was observed and analyzed using an optical microscope, mainly analyzing the precipitation of copper ions. The main parameters of the XRD test of the EuS / Cu2S test block are: Cu target K αThe line was operated at 40 kV, 20 mA, a scan step size of 0.02°, and a scan speed of 6° / min. The phase composition was confirmed by comparing the diffraction peaks with those of an orthorhombic Cu2S standard card (JCPDS#33-0490). The micromorphology, grain size, and elemental distribution of the EuS / Cu2S test piece were observed using a scanning electron microscope.

[0176] The mixed powder was weighed and placed in a dry corundum crucible and analyzed using a TG / DTA analyzer (NETZSCH STA449C, NETZSCH Thermogravimetric analysis was performed at the company's facility in Munich, Germany; the entire heating and cooling process was conducted in a nitrogen atmosphere. The thermoelectric performance of the EuS / Cu2S test piece was measured using a Seebeck coefficient / resistance measurement system to simultaneously measure the Seebeck coefficient (S), conductivity (σ), and carrier concentration.

[0177] After thermal analysis and electrical transport performance tests, the test results show that the EuS / Cu2S sintered block of this embodiment is used as a thermoelectric material, and the thermal stability temperature and electrical performance parameters are shown in Table 1 below.

[0178] Figure 13 is the XRD pattern of the EuS / Cu2S sintered block of this embodiment; Figure 14 This is the SEM image of the EuS / Cu2S sintered block of this embodiment.

[0179] Figure 13 In the figure, the XRD pattern of the EuS / Cu2S sintered block is the same as the PDF card pattern of Cu2S, indicating that the crystal form of the product remains unchanged after the addition of EuS. Figure 14 In the figure, the SEM and EDS images of the EuS / Cu2S sintered block show that after the addition of EuS, the Eu element is evenly distributed in the Cu2S matrix, forming a pinning effect.

[0180] Example 8

[0181] The only difference between this embodiment and embodiment 6 is that the step of grinding Cu2S and Sm2S3 in step (1) is omitted (this embodiment directly mixes Cu2S and Sm2S3 evenly before performing subsequent steps; the particle size of Cu2S in this embodiment is 40-50μm, and the particle size of Sm2S3 is 20-30μm); the rest is consistent with embodiment 6.

[0182] The electrical properties of the Sm2S3 / Cu2S test block of this embodiment were tested, and the test results are shown in Table 1 below.

[0183] Comparative Example 1

[0184] This control example serves as a blank control. The only difference between this control example and Example 1 is that the step of adding La2S3 in step (1) is omitted; the rest is consistent with Example 1.

[0185] After thermal analysis and electrical performance testing, the Cu2S test block of this comparative example has its thermal weight loss mass and electrical parameters as shown in Table 1 below.

[0186] Figure 15 This is an optical photograph of Cu2S prepared in this comparative example 1; Figure 15 It can be seen that a large amount of copper ions are precipitated on the surface of pure Cu2S after sintering, and the precipitated copper ions are enriched on the sample surface in the form of filaments.

[0187] Comparative Example 2

[0188] The difference between this control example and Example 2 is that an equal amount of Sb2S3 is used to replace Ce2S3 in Example 2; the rest is consistent with Example 2, and the Sb2S3 / Cu2S sintered block of this control example is obtained.

[0189] After thermal analysis and electrical transport performance tests, the Sb2S3 / Cu2S sintered block prepared in this embodiment was obtained as a thermoelectric material, and the thermal stability temperature and electrical performance parameters are shown in Table 1 below.

[0190] Figure 16 Optical photograph of Sb2S3 / Cu2S prepared in this comparative example 2; Figure 16 It can be seen that there are bulges on the surface of Sb2S3 / Cu2S after sintering, and the surface morphology is irregular.

[0191] Figure 17 This is the SEM image of Sb2S3 / Cu2S prepared in this comparative example 2. Figure 17 It can be seen that there are holes and cracks around Sb2S3 / Cu2S.

[0192] Comparative Example 3

[0193] The difference between this control example and Example 6 is that no pre-pressure is applied to the molding block in step (3); the rest are consistent with Example 6;.

[0194] Figure 18 This is an optical photograph of Sm2S3 / Cu2S prepared in this control example 3. It can be seen from the figure that in the absence of pre-pressure applied by the assembly mold, the surface of Sm2S3 / Cu2S has large deformation after sintering, and there are holes in the sample. Due to the low strength, it cannot be cut to test the electrical properties.

[0195] Comparative Example 4

[0196] The difference between this control example and Example 7 is that in step (3), the graphite paper disc is omitted (i.e., the bolt directly contacts the molding block and applies pre-pressure to the molding block); the rest is consistent with Example 7.

[0197] Figure 19 This is an optical photograph of EuS / Cu2S prepared in this control example. It can be seen from the figure that in the absence of graphite gaskets, the EuS / Cu2S sintered block is prone to breakage during the cooling process, destroying the geometric shape and size, and affecting the subsequent electrical performance test.

[0198] Table 1 Thermoelectric performance data of the examples and comparative examples (T = 477 ° C)

[0199]

[0200] As shown in Table 1, the light rare earth sulfide-modified cuprous sulfide thermoelectric material prepared in Examples 1-7 of the present invention, wherein the light rare earth sulfide Ln2S3 is added as a modifier to the cuprous sulfide thermoelectric material, significantly improves the stability and electrical transport performance of the cuprous sulfide thermoelectric material, significantly reduces the weight loss rate, and significantly improves the electrical transport performance. Furthermore, different light rare earth sulfides have different effects on improving the performance of the cuprous sulfide thermoelectric material. The process parameters selected, including the ratio of light rare earth sulfide to cuprous sulfide, the particle size of the solid mixture (the solid mixture obtained by mixing and pulverizing the light rare earth sulfide and cuprous sulfide), and the sintering temperature and time, have a critical impact on the performance of the light rare earth sulfide-modified cuprous sulfide thermoelectric material. Light rare earth sulfide as a modifier has different effects on the thermoelectric properties of cuprous sulfide.

[0201] In summary, the present invention adopts a method of hot pressing and sintering light rare earth sulfide and cuprous sulfide to prepare a light rare earth sulfide-modified cuprous sulfide thermoelectric material. The light rare earth sulfide-modified cuprous sulfide of the present invention is obtained by adjusting the particle size of a solid mixture of light rare earth sulfide and cuprous sulfide, cold pressing, applying pre-pressure through mold assembly, and hot pressing and sintering. The light rare earth sulfide-modified cuprous sulfide of the present invention is used as a thermoelectric material to improve the thermal stability of cuprous sulfide. The design of an anti-diffusion gasket and an isolation cylindrical ring in the assembly mold can reduce defects in the block, promote rapid hot pressing and sintering of the light rare earth sulfide-modified cuprous sulfide, and improve the density of the sintered block. At the same time, the addition of light rare earth sulfide does not affect the sintering and crystal structure of cuprous sulfide. The production equipment of the present invention is simple, can be mass-produced, is easy to operate, and is suitable for industrial promotion.

[0202] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.

Claims

1. A method for preparing a light rare earth sulfide modified cuprous sulfide thermoelectric material, characterized in that: The steps include: (1) crushing light rare earth sulfide, adding cuprous sulfide powder, mixing, crushing, and sieving to obtain a solid mixture; (2) cold pressing the solid mixture to obtain a molding block; (3) placing the molding block in a hot pressing sintering mold and applying pre-pressure to the molding block to obtain an assembled mold block; (4) placing the assembled mold block in a quartz tube of a tube furnace, performing hot pressing and sintering treatment under an inert atmosphere, and cooling to obtain the light rare earth sulfide modified cuprous sulfide thermoelectric material.

2. The method for preparing the light rare earth sulfide modified cuprous sulfide thermoelectric material according to claim 1, characterized in that: The molar ratio of the light rare earth sulfide to cuprous sulfide is (0.001-0.1):1; The light rare earth sulfide is at least one of La2S3, Ce2S3, Pr2S3, Nd2S3, Sm2S3, Y2S3 and EuS.

3. The method for preparing the light rare earth sulfide modified cuprous sulfide thermoelectric material according to claim 1, characterized in that: The hot pressing sintering temperature is 350-750°C and the holding time is 0.2-18h; The cooling is furnace cooling or cooling at a rate of 5-10K / h.

4. The method for preparing the light rare earth sulfide modified cuprous sulfide thermoelectric material according to claim 1, wherein: In step (1), the particle size of the solid mixture is ≤50 μm; Preferably, the particle size of the solid mixture is ≤10 μm; More preferably, the particle size of the solid mixture is ≤5 μm.

5. The method for preparing the light rare earth sulfide modified cuprous sulfide thermoelectric material according to claim 1, wherein: In step (2), the cold pressing pressure is 2-15 MPa, and the holding time is 1-300 min; Preferably, double-sided pressurization is adopted during the cold pressing process; after the molding block is taken out from the cold pressing mold, the step of placing it under inert atmosphere for 3-72 hours is also included.

6. The method for preparing the light rare earth sulfide modified cuprous sulfide thermoelectric material according to claim 1, characterized in that: In step (3), the pre-pressure is 1.5-40 MPa; Before the hot pressing and sintering process, the method further includes placing the assembled mold block in an inert atmosphere for 1-12 hours.

7. A light rare earth sulfide modified cuprous sulfide thermoelectric material, characterized in that: The light rare earth sulfide modified cuprous sulfide thermoelectric material is prepared by the method according to any one of claims 1 to 6.

8. A thermoelectric device, characterized in that The thermoelectric device adopts the light rare earth sulfide modified cuprous sulfide thermoelectric material according to claim 7; Preferably, the thermoelectric device is a thermoelectric power generation device or a thermoelectric refrigeration device.

9. A hot pressing sintering mold, characterized in that: The hot pressing sintering mold has an inner cavity and at least one opening, a pressure piece is provided through the opening, the inner cavity is used to accommodate the molding block, and the pressure piece is used to apply pre-pressure to the molding block; Preferably, there are two openings, and the two openings are symmetrically arranged relative to the molding block; More preferably, the pressure member is threadedly connected to the inner cavity of the hot pressing and sintering mold.

10. The hot pressing sintering mold according to claim 9, wherein: The inner cavity of the hot pressing and sintering mold is further equipped with an anti-diffusion gasket and / or an isolation cylindrical ring; the anti-diffusion gasket is arranged between the pressure member and the molding block; and / or the isolation cylindrical ring is arranged between the inner wall of the hot pressing and sintering mold and the molding block; Preferably, two anti-diffusion gaskets are provided, and the two anti-diffusion gaskets are respectively provided at both ends of the axial direction of the molding block; and / or the isolation cylindrical ring is provided along the circumference of the molding block; More preferably, the anti-diffusion gasket is a graphite paper disc; and / or the isolation cylindrical ring is made of cemented carbide.